“It is the Context, Stupid!”. Or is It? British-American Contributions to Electoral Geography since the 1960s - Herman van der Wusten; Virginie Mamadouh (L'Espace Politique)
‘Context’ has been a central notion in British-American electoral geography since the 1960s. Kevin Cox used it as the organizing concept for his seminal paper in Progress in Geography in 1969. The paper underlines the significance of Cox’s pioneering work and connects it to the work of two of the main authors during the following period: Ron Johnston and John Agnew. It then traces major lines of inquiry in electoral geography more generally and indicates the significance of notions of context in that wider frame. It ends with some indications of the now emerging research agenda for electoral geographers and with some notes on the gradual evaporation of earlier sharp divisions of a British-American realm of electoral geography versus others, and of strictly separated imaginations of sociologists/political scientists and geographers with respect to elections.